ANALISIS SENSITIFITAS TERHADAP KELAYAKAN FINANSIAL PERKEBUNAN KELAPA SAWIT RAKYAT DI DESA RAMBAH KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU (Studi kasus : Perkumpulan Perkebun Swadaya Kelapa Sawit Rambah Rokan Hulu) - Saprida, Saprida (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2024)
Financial Feasibility Analysis and Sensitivity Analysis of People's Oil Palm Plantation in Rambah Village, Rambah Hilir District, Rokan Hulu Regency. Prime University of Indonesia. This study aims to determine the Financial Feasibility Analysis and Sensitivity Analysis of People's Oil Palm Plantations in Rambah Village, Rambah Hilir District, Rokan Hulu Regency. The population in this study were oil palm farmers in Rambah Village, Rambah Hilir District, Rokan Hulu Regency, amounting to 100 families. The sample in this study was 31 families. The sampling technique of respondents was carried out using a simple random sampling technique which implies that each element of the population has the same opportunity to be a sample. This study uses quantitative methods. The data collection method used is by means of questionnaires, interviews and documentation. Net Present Value (NPV), Net Benefit Ratio (B/C), Internal Rate of Return (IRR), Payback Period (PP). The results showed that the Net Present Value (NPV) was positive, the Net Benefit Ratio (B/C was obtained at 1.90 Net B/C>1) then the oil palm plantation business using certified oil palm seeds was feasible to develop, Internal Rate of Return (IRR) of 35,91%, it is feasible to be developed, and the Payback Period (PP) is 3 years 8 months. Sensitivity analysis to a 10% price reduction is obtained by a Net Benefit Ratio (B/C of 1.49, Net B/C>1, Internal Rate of Return (IRR) of 26.26% and Payback Period (PP) of 4 years and 3 months. Sensitivity analysis to a 10% cost increase obtained a Net Benefit Ratio (B/C of 1.65, Net B/C>1, Internal Rate of Return (IRR) of 31.43% and Payback Period (PP) of 3 years and 10 months.